A Subtitling Analysis Of Verbs And Verb Phrases In TheMagic Of Belle Isle Movie - Kaffah, Silmi; , Dr. Dwi Haryanti, M. Hum; , Aryati Prasetyarini, S. Pd., M. Pd (2015)
The research paper studies about subtitling variations of verbs and verb phrases in movie The Magic of Belle Isle. The study aims at identifying the subtitling variations of verbs and verb phrases and describing the readability of subtitling of verbs and verb phrases in The Magic of Belle Isle movie. The research paper is a descriptive qualitative research. The data are sentences containing verbs and verb phrases found in the data source which is the subtitling variations. The data sources are from The Magic of Belle Isle movie and its subtitling and the informants. The data are collected from both manuscripts by using documentation. The researcher applies comparison in analyzing the data of the study, then open questionnair and review the raters. The results of the research show that: from 562 data of subtitling variations of verbs and verb phrases; 267 data or 47,51% verb is translated into verb, 9 data or 1,6% verb into verb phrase, 6 data or 1,07% verb into noun, 2 data or 0,35% verb into adjective, 2 data or 0,35% verb into adverb, 24 data or 4,27% verb is not translated. Therefore, there are 102 data or 18,15% verb phrase is translated into verb phrase containing VP1, VP2, VP3, VP4, VP5, VP6, VP7, VP8, VP9 into VPa, VPb, VPc, VPd. 2 data or 0,35% verb phrase into noun phrase, 3 data or 0,53% verb phrase into adjective phrase, 123 data or 21,9% verb phrase into verb, 3 data or 0,53% verb phrase into noun, 3 data or 0,53% verb phrase into adjective, 3 data or 0,53% verb phrase into adverb, 8 data or 1,43% verb phrase into interjection, 5 data or 0,9% verb phrase is not translated. Moreover, the readability of subtitling is divided into two, namely; high readability level and medium readability level. In the research paper, from 562 data there are 95,19% data belong to high readability level and 4,81% data belong to medium readability level. From these percentages, it can be concluded that the subtitling variations of verbs and verb phrases in The Magic of Belle Isle movie is readable